Designing M – RIES (Mental Retardation’s English Vocabularies) As Learning Media For Mild Mental Retardation Students - Anandita, Septian Ragil; Z, Abadi Kharisa Putri; Maarif, Iin Baroroh; Nur, Luluk Choirun Nisak (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
ABSTRACT English is a part of the curriculum in Indonesian schools and universities, even English is used as the extra lessons and programs developed in inclusive schools or local content specifically provided as the student’s knowledge of the language. The objective of the research is to designing M – RIES (Mental Retardation English Vocabularies) as learning media for mild mental retardation students. The researcher used Research and Development (R&D) methods. In this research procedure adapts ADDIE model that consist of five stages. Those are: analysis, design, development, implementation, and evaluation. The researcher used observation and questionnaire to collect the data. This media has been validated by 4 experts before being implemented to the students. The result of the material experts validator obtained 82,5% and 90% in the “Strongly Agree” category. In addition, the result of media experts validator obtained 89,4 % and 96,4% that was also include in “Strongly Agree” category. The researcher conducted trials on 4 mild mental retardation students at SMALB Tunas Harapan 1 Tembelang. The result of implementation obtained 95% were in “Very Good” category. By having those results, this M – RIES media is feasible to be used as learning media for mild mental retardation students. Key words:  Learning Media, Mild Mental Retardation, M – RIES, R&D, Vocabularies ABSTRAK Bahasa Inggris menjadi bagian dari kurikulum di sekolah-sekolah dan universitas di Indonesia, bahkan bahasa Inggris digunakan sebagai pelajaran tambahan dan program-program yang dikembangkan di sekolah inklusif atau muatan lokal yang disediakan secara khusus untuk pengetahuan bahasa siswa. Tujuandaripenelitianiniadalahmerancang M – RIES (Mentall Retardation English Vocabularies) sebagai media pembelajaran untuk siswa dengan keterbelakangan mental ringan. Peneliti menggunakan metode Penelitian dan Pengembangan (R&D). Dalam prosedur penelitian ini, digunakan model ADDIE yang terdiri dari lima tahap, yaitu: analisis, desain, pengembangan, implementasi, dan evaluasi. Peneliti menggunakan observasi dan kuesioner untuk mengumpulkan data. Media ini telah divalidasi oleh 4 pakar sebelum diimplementasikan kepada siswa. Hasil dari validator ahli materi didapatkan sebesar 82,5% dan 90% dalam kategori "Sangat Setuju". Selain itu, hasil dari validator ahli media didapatkan sebesar 89,4% dan 96,4% yang juga termasuk dalam kategori "Sangat Setuju". Peneliti melakukan ujicoba pada 4 siswa tunagrahita ringan di SMALB Tunas Harapan 1 Tembelang. Hasil implementasi didapatkan sebesar 95% dalam kategori "Sangat Baik". Dengan hasil tersebut, media M – RIES ini layak digunakan sebagai media pembelajaran bagi siswa dengan keterbelakangan mental ringan. Kata kunci: Kosakata, M – RIES, Media Pembelajaran, Tunagrahita ringan, R&D